Effects of presentation speed of a dynamic visualization on the understanding of a mechanical system - Fischer, S.; Lowe, Ric; Schwan, S. (Lawrence Erlbaum Associates Inc., 2006)
In an experimental study, the role of temporal variation of a realistic animation was examined. The animation of a complex mechanical system, a pendulum clock, was presented in a between subject design at normal or fast speed. Presentation speed was found to affect distribution of attention and understanding of the functionality of the clockwork mechanism. Verbal reports in the fast condition contained more statements on the weight, which is a central part of the clocks’ mechanism. When giving a written description of the clock, subjects who saw the fast presentation produced more correct and less false concepts about the key components of the clock- work. For complex subject matter, it seems possible that speed could be used strategically by instructional designers to raise the perceptual salience of thematically relevant aspects of the display, by means of faster or slower presentation speeds